Understanding leadership roles and competencies for public-private partnership. Issue 4 (20th February 2020) - Mohd Som, Rafedzah; Omar, Zoharah; Ismail, Ismi Arif; Alias, Siti Noormi
Abstract : Purpose: The purpose of this study is to explore the roles of public–private partnership (PPP) leaders and the vital skills and competencies that PPP leaders should possess to ensure the success of PPP projects in Malaysia. Design/methodology/approach: This study adopted an exploratory qualitative research design using an in-depth interview technique. Ten informants who were involved in the PPP projects from the public and the private sectors participated in this study. Data gathered from the in-depth interview were analysed using the constant comparative method. Findings: The findings of this study show that among the main roles of PPP leaders are building a collaborative culture, leading and influencing the partnership process by developing trust and encouraging commitment and fairness. Key competencies were sensitivity of the cross-cultural issues between the public and the private sector, communication and PPP technical skills. Practical implications: This paper outlines key competencies for the training and selection of PPP leaders and team members. Originality/value: This paper enriches the existing body of knowledge on Malaysia's PPP with regard to PPP leadership roles and their competencies.